CORPORATE SOCIAL AND ENVIRONMENTAL DISCLOSURES AND MARKET VALUE OF LISTED FIRMS IN NIGERIA - Okwy Peter Okpala; Oluwamayowa Olalekan Iredele (Copernican Journal of Finance & Accounting, 2019)
This study examines the effect of corporate social environmental disclosure (CSED) on the market value of eighty-four (84) listed firms in Nigeria, which were purposively selected from the period 2011 to 2016. The aggregate of (CSED) were regressed on Market Value (Tobin’s Q), while Firm size, financial performance, board size, leverage, affiliation to foreign company and industry type were factored in as extraneous variables. Data were obtained through content analysis of annual reports of sampled firms and were analysed through descriptive statistics and regression analysis. The result of the descriptive analysis showed that the mean score for the CSED is above average and the standard deviation for almost all the variables is low which indicated that the deviation of the actual data from their mean is not significant. The OLS result revealed that CSED, firm size, financial performance, affiliation with foreign company and industry type have significant effect on the market value of firms, while Board size and leverage do not significantly influence the market value of firms. The study recommends that firms should disclose information on their environmental performance as a way of adding value.